Prevalence and Impact of Apolipoprotein E7 on LDL Cholesterol Among Patients With Familial Hypercholesterolemia - Tada, Hayato; Yamagami, Kan; Kojima, Nobuko; Shibayama, Junichi; Nishikawa, Tetsuo; Okada, Hirofumi; Nomura, Akihiro; Usui, Soichiro; Sakata, Kenji; Takamura, Masayuki; Kawashiri, Masa-aki (Frontiers in Cardiovascular Medicine, 2021)
Background: It has been suggested that a rare mutant apolipoprotein E7, APOE7 (p.Glu262Lys, p.Glu263Lys), has been identified to be associated with hyperlipoproteinemia in the general population. Moreover, its prevalence has been shown to be 0.005–0.06%. However, there are no prior data regarding its prevalence and impact on serum lipids in patients with familial hypercholesterolemia (FH). Methods: We recruited 1,138 patients with clinically diagnosed FH [mean age = 48, men = 512, median low-density lipoprotein (LDL) cholesterol = 231 mg/dl]. The coding regions of three FH genes (LDLR, APOB, and PCSK9) and apolipoprotein E (APOE) gene were sequenced. We investigated the prevalence and impact of APOE7 mutant on serum lipid levels in patients with FH. Results: We identified 29 patients (2.5 %) with a mutant APOE7 (heterozygote), which is apparently much higher than that of the general population. Moreover, when we focus on those without FH mutation (n = 540), we identified 21 patients (3.9 %) with a mutant APOE7. Patients with a mutant APOE7 exhibited significantly higher median LDL cholesterol and triglyceride levels compared with those without this rare mutant (249 vs. 218 mg/dl, p < 0.05, 216 vs. 164 mg/dl, p < 0.05, respectively). Moreover, LDL cholesterol levels in the APOE7-oligogenic FH individuals, with a pathogenic mutation in FH genes and APOE7 mutant, were significantly higher than that in monogenic FH patients (265 vs. 245 mg/dl, p < 0.05). Conclusion: We identified more patients with a mutant APOE7 than expected among those diagnosed with FH clinically, especially among those without FH-causing mutation. This implies a mutant APOE7 may be one of the causes FH, especially among those without FH mutations.